Removal of mercury from petroleum sludge using chemical treatment - Muhammad Fauzi Ahmad, 1987-; Wan Azelee Wan Abu Bakar; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2009